Assessment of cardiac mechanics and biomarkers during headache attack in migraine patients with aura: a prospective study - Gökdeniz Tayyar; Kalaycıoğlu Ezgi; Bernas, Altıntaş (The International Journal of Cardiovascular Imaging, 2020)
Migraine with aura (MA) was found to be associated with increased cardiovascular events (CVE), whereas left ventricular (LV) mechanics were not previously studied in migraineurs. In this study, we aimed to assess LV functions with the utility of two-dimensional speckle tracking echocardiography (2D-STE) and cardiac biomarkers with respect to the headache-free and attack periods and frequency of migraine attacks. Sixty-eight patients with MA were enrolled. During headache-free and attack periods, all patients underwent echocardiographic examination including 2D-STE, and cardiac biomarkers, B-type natriuretic peptide (BNP) and high sensitive cTnT (hs-cTnT) were studied. The impact of headache periods and frequency of attacks on cardiac mechanics and biomarkers were investigated. The mean age of study population was 38.1 ± 7.7 years (56 female) and thirty-one patients (44.6%) had high-frequency migraine attacks. Patients who suffered headache-attack periods had higher frequency of detectable hs-cTnT levels and increased NT-proBNP values which did not differ between low- and high-frequency migraine groups in both periods. Headache attack periods had decreased global longitudinal strain (GLS), increased LV end-systolic volume (LVESV), E/Em ratio and LV torsion (LV-tor) during headache-attack periods. In multivariate analysis; LVESV, LV-tor and high frequency of migraine attacks were associated with decreased GLS (≤ − 20.8), (p 0.038, p 0.026 and p 0.013, respectively). Consequently, 2D-STE findings revealed that migraine attacks, especially with increasing frequencies, could have negative impact on LV mechanics, which adds a new perspective about increased CVE in subjects with MA.